La democracia combate la corrupcíon (1994)
"A collection of papers and reflections on various aspects of corruption in post-military Chile. The presentations by former and current government officials, leading entrepreneurs, and others tell the reader little about the extent of problem, but make clear how a person's vantage point colors his (or her) perceptions of and preferred solutions for these problems"--Handbook of Latin American Studies, v. 57